The Relationship Between Service Quality and Students Satisfaction Among Students in Kias, Nilam Puri, Kelantan - Saufi, Suraini; Muhammad Razaki, Marina (RABBANICA - Journal of Revealed Knowledge, 2020)
Service quality is crucial for higher education institutes to gain competitive advantages and growth, especially for private institutions. The current research paper aims to examine the relationship between service quality and student satisfaction. Data was collected from 306 students of KIAS from 7 departments. Multiple regression was used to analyze the data. Responses from the student were measured through an adapted questionnaire where 5-point Likert scale was applied. The results from regression analyses showed that there were three factors, namely: Tangibility; Guarantee; and Empathy that directly affect students’ satisfaction. The key findings of this study suggest that the administration of KIAS needs to understand the changing factors that shape students’ satisfaction and beware of its existing service quality provided for the students. Due to that, the potential strategies and service improvement should be planned accordingly to cater to the students’ needs and expectations.